Indigenous production and interregional exchange: late second-millennium BC bronzes from the Hanzhong basin, China - Kunlong Chen (14758150) (2016)
Traditional studies of early bronze metallurgy in China have focused on typology, decoration and production methods. The application of new analytical techniques to investigate chemical composition, however, is offering important new insights. The use of one such method (electron probe microanalysis) to study bronze artefacts from the Hanzhong basin in central China shows a level of diversity that implies much greater complexity in the extended landscape networks of the Bronze Age than was previously thought. The ability to appreciate these finds from a new perspective allows progression beyond older, simplistic models, and demonstrates that the Hanzhong region held greater importance within the power structure of Bronze Age Central China than has previously been recognised. Other Information Published in: Antiquity License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.15184/aqy.2016.94